SISTEM PENDIDIKAN DI PONDOK PESANTREN MANSYAUL ULUM CONGKOP NAGASARI TLAMBAH KECAMATAN KARANG PENANGKABUPATEN SAMPANG - Haris, Abd (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
The educational system is an interrelated components amongst one to another. The success of an organization of education is depend on the education system itself, because a good education system will produce the best output, mansyaul ulum boarding school is the organizing educational institutions use a good education system. The education systems in the Mansyaul Ulum Congkop boarding school are the classical and modern education systems. the classical method is going to use sorogan, lectures, recitation while the modern of education system is implemented by using new methods such as meetings or discussions, lectures, discussion, group works and others. The process of education at Mansyaul Ulum boarding school are: a) the educational process using a curriculum governments of both MONE and MORA the educational activities carried out in the morning up to noon, b) the educational process using their own curriculum is designed by Mansyaul Ulum boarding school itself, c) besides that, there are also extra education students in the form of Arabic and English courses, scouting qiroat, recite and the writing improvement skill. Thus the expected results of this research can be input for the entire community of Mansyaul Ulum boarding school for more advanced and better in the future.